CHARACTERIZATION ASSESSMENT OF RECYCLED EMULSION COLD MIXTURES CONTAINING HIGH PERCENTAGES OF RECLAIMED MATERIALS - AL-JUMAILI, MOHAMMED ABBAS (Journal of Duhok University, 2017)
Cold recycling (CR) is a partial recycling process through which a portion of the existing recycled asphalt pavement (RAP) material is rejuvenated and placed back on the road as a new surface course without introducing heat during the recycling process for low volume roadways .Recycling cold mixtures produced by  incorporating milled old asphalt runway pavement into some new aggregate and cement as a filler material . During the past few years, the utilization of new processing machines has created expanding measures of reclaimed asphalt materials (RAP).These quantities of RAP have been obtained by milling of in-service and deteriorated flexible pavement in Najaf city located to south of Baghdad city by 160 km . While numerous agencies all around the world have adopted the practice of recycling, only a rare number of research studies have been performed to characterize and examine the strength, durability, and suitability of recycling techniques on local materials in Iraq. Comparison have been achieved between curing time effect in lab ( 1, 7 ,14 , 28 , 56 and 90 days ) on soaked stability , air voids moisture absorbed (%) and rut depth , and effect of accumulated service time (14,28,56,90,120,150,180and 240 days ) on those properties . the rut depth of test road at service time of 240 days gave value is similar to that at curing time of 28 days.